(untitled) (Teología, 2020)
The author intends to observe the search for God in some expressions of contemporary pictorial art. The artists selected for the tour are Georges Rouault, Stephen Koek Koek, William Congdon and Santiago García Sáenz. They represent a span of life and diverse backgrounds between 1871 and 2006. This article presents the life and work of each of them and sets out the content of their iconological language. As a final synthesis, the theological perspectives open by these four artists of our time are discussed.